2004
DOI: 10.1039/b314592c
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation of interfacial properties in liquid systems: assessment of harmonic distortion

Abstract: The total harmonic distortion (THD) parameter is applied to oscillation experiments involving interfacial phases. The THD-value appears a suitable index which can be used for a quantitative estimation of the goodness of the linearity hypothesis, as assumed in the theoretical interpretation of the interfacial excitation-response behaviour. Example experimental results grant a validity domain of the linearity hypothesis and an amplitude-range tolerability for the external forcing excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…In addition to the analysis described in this paper, the observed surface oscillation response could be expanded in a Fourier series 16,17 or a series of Chebyshev polynomials. 15 However, we believe that in this situation the graphical presentation leads to more insight.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the analysis described in this paper, the observed surface oscillation response could be expanded in a Fourier series 16,17 or a series of Chebyshev polynomials. 15 However, we believe that in this situation the graphical presentation leads to more insight.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, the THD-parameter was used to quantify the inaccuracies of dosing system and disturbances [35,36]. We show that THD is significantly influenced by a, but is not influenced by f. Generally, a nonlinearity appears at higher a. Saulnier et al [32] found that nonlinear phenomena appear for a DPPC monolayer when a > 10%.…”
Section: Dependence Of η and ε On Oscillation Frequency And Amplitudementioning
confidence: 97%
“…Inaccuracies of dosing and disturbances were quantified by the total harmonic distortion (THD) [35,36], expressed as a percentage of a 1 :…”
Section: Surface Rheology Measurementsmentioning
confidence: 99%
“…The excitation-response behavior of the drop needs to be in linearity for a harmonic behavior. If the relationship is non-linear, the system shows non-harmonic distortion which can result in severe a calculation mistake [30]. The harmonic distortion was observed.…”
Section: Dilatational Rheologymentioning
confidence: 99%
“…So far, no study systematically analyzed the applicability of the interfacial methods at an increased concentration far beyond the common concentrations of 1-2%. However, the suitability of the measurement equipment as well as the model-based calculations can be verified via specific indicators for accuracy of measurement and calculation [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%